Emerging Technologies in Computing : Third EAI International Conference, ICETiC 2020, London, UK, August 19-20, 2020, Proceedings.: Third EAI International Conference, ICETiC 2020, London, UK, August 19-20, 2020, Proceedings. ([2020]) - Unknown
No abstract available